Standar Akuntansi Pemerintah Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Pemda - Jecklin Eman; Lukman Pakaya; Ayu Wuryandini (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2022)
The research aims to determine the impact of Government Accounting Standard and Human Resource Competence on the Financial Statement Quality in Regional Government of Gorontalo Regency. Method applied in this research is quantitative descriptive. The data collected are primary data obtained from questionnaire distributed to employees in Financial Agency of Gorontalo Regency. The research findings are 1) the Government Accounting Standard owns a positive and insignificant impact on the financial statement quality, 2) the Human Resource Competence owns a positive and insignificant impact on the financial statement quality, and 3) the Government Accounting Standard and Human Resource Competence, simultaneously, own an insignificant impact on the financial statement quality.